Preclinical evaluation of (S)-[18F]GE387, a novel 18-kDa translocator protein (TSPO) PET radioligand with low binding sensitivity to human polymorphism rs6971 - Ramakrishnan, Nisha K.; Hird, Matthew; Thompson, Stephen; Williamson, David J.; Qiao, Luxi; Owen, David R.; Brooks, Allen F.; Scott, Peter J. H.; Bacallado, Sergio; O’Brien, John T.; Aigbirhio, Franklin I. (European journal of nuclear medicine and molecular imaging, 2021)
Purpose Positron emission tomography (PET) studies with radioligands for 18-kDa translocator protein (TSPO) have been instrumental in increasing our understanding of the complex role neuroinflammation plays in disorders affecting the brain. However, ( R )-[ 11 C]PK11195, the first and most widely used TSPO radioligand has limitations, while the next-generation TSPO radioligands have suffered from high interindividual variability in binding due to a genetic polymorphism in the TSPO gene (rs6971). Herein, we present the biological evaluation of the two enantiomers of [ 18 F]GE387, which we have previously shown to have low sensitivity to this polymorphism. Methods Dynamic PET scans were conducted in male Wistar rats and female rhesus macaques to investigate the in vivo behaviour of ( S )-[ 18 F]GE387 and ( R )-[ 18 F]GE387. The specific binding of ( S )-[ 18 F]GE387 to TSPO was investigated by pre-treatment with ( R )-PK11195. ( S )-[ 18 F]GE387 was further evaluated in a rat model of lipopolysaccharide (LPS)-induced neuroinflammation. Sensitivity to polymorphism of ( S )-GE387 was evaluated in genotyped human brain tissue. Results ( S )-[ 18 F]GE387 and ( R )-[ 18 F]GE387 entered the brain in both rats and rhesus macaques. ( R )-PK11195 blocked the uptake of ( S )-[ 18 F]GE387 in healthy olfactory bulb and peripheral tissues constitutively expressing TSPO. A 2.7-fold higher uptake of ( S )-[ 18 F]GE387 was found in the inflamed striatum of LPS-treated rodents. In genotyped human brain tissue, ( S )-GE387 was shown to bind similarly in low affinity binders (LABs) and high affinity binders (HABs) with a LAB to HAB ratio of 1.8. Conclusion We established that ( S )-[ 18 F]GE387 has favourable kinetics in healthy rats and non-human primates and that it can distinguish inflamed from normal brain regions in the LPS model of neuroinflammation. Crucially, we have reconfirmed its low sensitivity to the TSPO polymorphism on genotyped human brain tissue. Based on these factors, we conclude that ( S )-[ 18 F]GE387 warrants further evaluation with studies on human subjects to assess its suitability as a TSPO PET radioligand for assessing neuroinflammation.